Measuring coping in multiple sclerosis: The Coping Index-MS. (December 2022) - Young, Carolyn A; Mills, Roger J; Langdon, Dawn; Rog, David J; Sharrack, Basil; Kalra, Seema; Majeed, Tahir; Footit, David; Harrower, Tim; Nicholas, Richard S; Ford, Helen L; Woolmore, John; et al.
Background: Coping in multiple sclerosis (MS) refers to cognitive and behavioural efforts to manage stresses imposed by the illness. Existing generic and disease-specific coping scales do not meet modern guidelines for scale development and cannot produce interval-level metrics to allow for change scores. Objective: The main aim of this study was to develop a brief patient-reported outcome measure for coping in MS, capable of interval-level measurement. Methods: Qualitative work in 43 people with MS leads to a draft scale which was administered to 5747 participants, with longitudinal collection in 2290. A calibration sample of 1000 subjects split into development and validation sets was used to generate three scales consistent with Rasch model expectations. Results: The total Coping Index-MS (CI-MS-T), CI-MS-Internal (CI-MS-I) and CI-MS-External (CI-MS-E) cover total, internal and externally focused coping. All three scales are capable of interval-level measurement. Trajectory analysis of 9000 questionnaires showed two trajectories in CI-MS-T: Group 1 showed a low level of coping with slight decline over 40 months, while Group 2 had a better and stable level of coping due to improving CI-MS-I which compensated for the deteriorating CI-MS-E over time. CI-MS-T < 30 identified group membership at baseline. Conclusion: The CI-MS-T, CI-MS-I and CI-MS-E, comprising 20 items, provide interval-level measurement and are free-for-use in not-for-profit settings.